2014
DOI: 10.1016/j.jegh.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink usage among university students in a Caribbean country: Patterns of use and adverse effects

Abstract: Energy drink usage is prevalent among students. The use is not excessive, but associated with high rates of adverse effects and occurs in potentially dangerous situations like during exercise and with alcohol. There is a need to educate students about the potential adverse effects of energy drinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 32 publications
6
60
2
10
Order By: Relevance
“…. As bebidas energéticas foram o estimulante mais consumido (38%), com frequência similar à de estudos anteriores 14,15,20 . A cafeína foi a segunda mais consumida, apresentando prevalência de consumo inferior à encontrada em estudos prévios 14,15,21,22 , porém esses estudos não delimitaram quantidade e/ou frequência de consumo mínimas, como foi feito neste estudo.…”
Section: Resultsunclassified
“…. As bebidas energéticas foram o estimulante mais consumido (38%), com frequência similar à de estudos anteriores 14,15,20 . A cafeína foi a segunda mais consumida, apresentando prevalência de consumo inferior à encontrada em estudos prévios 14,15,21,22 , porém esses estudos não delimitaram quantidade e/ou frequência de consumo mínimas, como foi feito neste estudo.…”
Section: Resultsunclassified
“…For example, 28.4% (n = 96) believed that studying for exams or finishing a project was a reason for using energy drinks, 88 college students (26%) reported using energy drinks for gaining energy (speed, strength, power), whereas 23.4% (n = 79) reported enhanced academic performance as their reason for using energy drinks. In another recent study, energy drinks were most commonly used to increase energy (50%), combat sleepiness (45%) enhance academic performance (40%), and enhance performance during sports (23%) [17]. In an additional study, it was found that the main reason for energy drink consumption among college students was to support studying for exams or completing a project (31.4%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most consumers are teenagers and young adults [3,4]. University medical, sports and arts students are more likely to consume these beverages [3,5]. Several studies reported that the common motivation for consumption was to obtain better grades and attenuate the effects of alcohol [6].…”
Section: Introductionmentioning
confidence: 99%